2019
DOI: 10.1038/s41419-019-1508-2
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow-derived mesenchymal stem cells promote colorectal cancer progression via CCR5

Abstract: Mesenchymal stem cells (MSCs) are recruited from BM to the stroma of developing tumors, where they serve as critical components of the tumor microenvironment by secreting growth factors, cytokines, and chemokines. The role of MSCs in colorectal cancer (CRC) progression was controversial. In this study, we found that C-C chemokine receptor type 5 (CCR5) ligands (i.e., C-C motif chemokine ligand 3 (CCL3), CCL4, and CCL5) were highly produced from MSCs using a chemokine array screening with conditioned media from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 54 publications
4
70
0
Order By: Relevance
“…13 Therefore, either prevention of the metastatic stage or expanded therapeuticespecially immunotherapeuticoptions, are in the focus of current research. 39 Our histological analysis of primary tumors showed an even distribution of CCR5 expression across the whole tissue sections, without predominance in invasive parts of the tumor, and is in accordance to previously published studies: CCR5 was expressed by cancer cells, 40,41 by tumor-infiltrating lymphocytes 32 as well as by macrophages. 18 We additionally illustrate that CCR5 expression levels increase during primary tumor growth and peak in liver metastases, corroborating the hypothesis that CCR5 promotes metastasis.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…13 Therefore, either prevention of the metastatic stage or expanded therapeuticespecially immunotherapeuticoptions, are in the focus of current research. 39 Our histological analysis of primary tumors showed an even distribution of CCR5 expression across the whole tissue sections, without predominance in invasive parts of the tumor, and is in accordance to previously published studies: CCR5 was expressed by cancer cells, 40,41 by tumor-infiltrating lymphocytes 32 as well as by macrophages. 18 We additionally illustrate that CCR5 expression levels increase during primary tumor growth and peak in liver metastases, corroborating the hypothesis that CCR5 promotes metastasis.…”
Section: Discussionsupporting
confidence: 92%
“…48 Finally, CCR5 expression in colorectal cancer primary tumors were recently found to be associated with a shorter overall survival. 41 Not a single colorectal cancer liver metastasis in our hand contained only CCR5-negative tumor cells in all our analyzed samples so far. However, liver metastases exhibited patchiness in CCR5 immunostainings, i.e.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…On the other hand, the use of CCR5 blockers has been increasingly explored, and several studies support the use of this technology for the treatment of different diseases. For example, CCR5 blockers have a good potential for treating various types of cancer (Halama et al, 2016; Halvorsen et al, 2016; Mencarelli et al, 2013; Nishikawa et al, 2019; Pervaiz et al, 2019; Sicoli et al, 2014; Tanabe, Sasaki, Mukaida, & Baba, 2016; Velasco‐Velázquez et al, 2012), graft‐versus‐host disease (Moy et al, 2017; Reshef et al, 2019), inflammatory bowel disease (Mencarelli et al, 2016) and stroke (Joy et al, 2019). Therefore, the lack of CCR5 is deleterious in some situations, but blocking this receptor may be desirable in specific clinical contexts.…”
Section: Introductionmentioning
confidence: 99%
“…CCL5 (C-C motif chemokine ligand 5) is a member of the C-C chemokine family, and acts as a potent chemoattractant of T cells, basophils, eosinophils, and macrophages [6]. It has been shown that the main producer of tumor associated CCL5 is not the cancer cells, rather the local mesenchymal stem cell population [7,8]. The literature is unanimously agreed on the pro-oncogenic impact of CCL5 on invasive breast tumors [6,9].…”
Section: Introductionmentioning
confidence: 99%